Plan de negocios para la creación de una empresa dedicada a la producción y comercialización de té de burbujas - Ayala Naranjo, María Salomé (2017)
The creation of a bubble tea shop is a project that will be carried out in the north of the city of Quito, the analysis both internal and external gives us important information about the beverage market and the current situation of the country allowing Make decisions on the investment of this project. In the beverage industry with an annual growth of 1porcent according to the Central Bank of Ecuador, it has a very strong competition due to the amount of substitute products bubble tea has, that is why it will have added value by delivering not only four types of tea, but also add tapioca and explosive bubbles. Bubble tea is a Taiwanese-origin drink consisting of an infusion of tea, a fruit syrup, tapioca bubbles and bubbles of exploding flavors, you can prepare it both hot and cold. The market research provided important information about the target audience, young people between 15 and 35 years old are willing to try different and novel products with 96.4 porcent acceptance of the product. The proposal of value is in addition to a product of quality and innovative a service of warmth with which customers feel at ease and seek to return to the store. The initial investment is approximately thirty-three thousand dollars which will be financed with 50 porcent of debt and 50 porcent of capital of the partners with a rate of return of one and a half years;; And with liquidity above the average of the beverage industry.